Analisis Aktivitas Fisik Pekerja Mal Pelayanan Publik Kota Cilegon - Mulya, Muhammad Syifa Abdy; Susilowati, Indri Hapsari Hapsari (National Journal of Occupational Health and Safety, 2024)
Physical activity is important because it has so many benefits. Even so, there are still many workers who are exposed to the risk of lack of physical activity. For this reason, it is necessary to know what affects the implementation of physical activity in workers. Quantitative design was used with a cross sectional study on 58 Cilegon Public Service Mall workers who met the criteria. As a result, 65.5% of workers are classified as active, 34.5% of workers are inactive and 12% of workers do not carry out any physical activity at all. Level of education (p value = 0.005), perceived benefits (P value = 0.01), friend support (p value = 0.014), body mass index (p value = 0.018), and family support (p value = 0.05) are the components that affect the implementation of physical activity in Cilegon Public Service Mall. Things that can be done to improve the implementation of physical activity include providing physical activity facilities, implementing group exercises, stretching instructions between work, and educating on physical activities. It is hoped that after conducting this research, the physical activity of Cilegon City Public Service Mall workers can be increased. Keywords: physical activities, lack of physical activities, Cilegon public service mall, office workers.